Early reconstruction of the ilioinguinal lobed flap in the treatment of facial and neck sulfuric acid burn: A case report - Jun-Hui Xu; Wei Zhang (Trauma Case Reports, 2025)
Objective: To investigate the therapeutic effect of an ilioinguinal lobed flap in the early repair of facial and neck injuries caused by sulfuric acid burn. Methods: A retrospective analysis was carried out on the case of a 29-year-old female patient with sulfuric acid burns. Initially, a left ilioinguinal lobed flap measuring 25 × 8 cm2 was selected to reconstruct the neck wound. Subsequently, a right ilioinguinal lobed flap was chosen to repair the facial wound. The flap consisted of three lobes, the longest diameter of which measured 29 cm and the shortest was 3.5 cm. During the surgery, the skin flap was dissected in the superficial fascia layer using ultrasound guidance, and the blood flow and anastomosis quality of the flap was ensured through vascular pressurization and fluorescence imaging. Results: The facial and neck flap transplantation procedure was successfully completed, with complete postoperative flap survival. Both the left and right ilioinguinal donor sites were closed in a single-stage. Wound healing was satisfactory with minimal and concealed scarring. Postoperative facial and neck contour was satisfactory. Conclusion: Early-stage repair of sulfuric acid burn wounds using free flaps is effective. Based on the anatomical characteristics of perforating branches in the ilioinguinal region, a superficial fascial flap was harvested with lobulation of the secondary perforating branch, enabling multi-vessel supercharged anastomosis with intraoperative fluorescence imaging to facilitate early and successful reconstruction of acid burn wounds.